Prevalence of Histological Gastritis in a Community Population and Association with Epigastric Pain - Zuzek, Rachael; Potter, Michael; Talley, Nicholas J.; Agréus, L.; Andreasson, A.; Veits, Lothar; Vieth, Michael; Walker, M. M. (Digestive Diseases and Sciences, 2023)
Background and Aims: Gastritis is a common histological diagnosis, although the prevalence is decreasing in developed populations, alongside decreasing prevalence of H. pylori infection. We sought to determine the prevalence of the etiology of gastritis in a Swedish population sample and to analyze any associations with symptoms, an area of clinical uncertainty. Methods: Longitudinal population-based study based in Östhammar, Sweden. A randomly sampled adult population completed a validated gastrointestinal symptom questionnaire (Abdominal Symptom Questionnaire, ASQ) in 2011 (N = 1175). Participants < 80 years of age and who were eligible were invited to undergo esophagogastroduodenoscopy (EGD) (N = 947); 402 accepted and 368 underwent EGD with antral and body biopsies (average 54.1 years, range 20–79 years; 47.8% male) with H. pylori serology. Results: Gastritis was found in 40.2% (148/368; 95% CI 35.2–45.2%). By rank, the most common histological subtype was reactive (68/148; 45.9%), then H. pylori (44/148; 29.7%), chronic non-H. pylori (29/148; 19.6%), and autoimmune (4/148; 2.7%). Gastritis was significantly associated with older age and H. pylori status (p < 0.01). Gastritis subjects were divided into three histological categories: chronic inactive inflammation, autoimmune gastritis, and active inflammation; there was no difference in the presence of upper gastrointestinal symptoms when categories were compared to cases with no pathological changes. Functional dyspepsia or gastroesophageal reflux were reported in 25.7% (38/148) of those with gastritis (any type or location) versus 34.1% (75/220) with no pathological changes (p = 0.32). Epigastric pain was more common in chronic H. pylori negative gastritis in the gastric body (OR = 3.22, 95% CI 1.08–9.62). Conclusion: Gastritis is common in the population with a prevalence of 40% and is usually asymptomatic. Chronic body gastritis may be associated with epigastric pain, but independent validation is required to confirm these findings. Clinicians should not generally ascribe symptoms to histological gastritis.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Endoscopy; Epigastric pain; Gastritis; H. pylori; Prevalence